Secreted Frizzled related protein-4 (sFRP4) promotes epidermal differentiation and apoptosis - Maganga, R.; Giles, N.; Adcroft, K.; Unni, A.; Keeney, D.; Wood, F.; Fear, M.; Dharmarajan, Arunasalam (Academic Press, 2008)
The skin provides vital protection from infection and dehydration. Maintenance of the skin is through a constant program of proliferation, differentiation and apoptosis of epidermal cells, whereby proliferating cells in the basal layer differentiating to form the keratinized, anucleated stratum corneum. The WNT signalling pathway is known to be important in the skin. WNT signalling has been shown to be important both in epidermal development and in the maintenance and cycling of hair follicles and epidermal stem cells. However, the precise role for this pathway in epidermal differentiation remains unknown. We investigated the role of the WNT signalling inhibitor sFRP4 in epidermal differentiation. sFRP4 is expressed in both normal skin and keratinocytes in culture. Expression of sFRP4 mRNA and protein increases with keratinocyte differentiation and apoptosis, whilst exposure of keratinocytes to exogenous sFRP4 promotes apoptosis and expression of the terminal differentiation marker Involucrin. These data suggest sFRP4 promotes epidermal differentiation. © 2008 Elsevier Inc. All rights reserved.